Công tác mô tả nội dung tài liệu tại Thư viện Học viện Chính trị Quốc gia Hồ Chí Minh : Khóa luận tốt nghiệp - Đỗ, Thị Phương Lân (2000)
Công tác mô tả nội dung tài liệu tại Thư viện Học viện Chính trị Quốc gia Hồ Chí Minh.